The Ways of Seeing and Making in Ali Smith's How to Be Both. Issue 3 (27th May 2022) - Cheong, Adel
ABSTRACT: There are, at least, two modes of experience when we encounter the pictorial and verbal in the Penguin UK paperback edition of Ali Smith's How to be both (2014). One aspect of Smith's work that deserves closer attention is the relationship between the visual and verbal, particularly in relation to the use of a reprinted artwork as cover art and its reappearance as an ekphrastic object in the narrative. This essay focuses on the reprinted photograph as a paratextual element in order to examine the ways in which photography is deployed as an embedded commentary on ways of seeing and making in the novel. The ekphrastic descriptions of artworks problematize the boundaries between fictive worlds and external reality. Therefore, might ekphrasis be deployed as a self-conscious maneuver aimed at revealing the artifice of these fictive worlds in the novel? Smith's exploration of duality extends to the crossing of boundaries between art forms, paratext and text, and image and word. Although this essay does not discuss duality in the context of gender and sexuality, it illustrates the ways in which How to be both encourages ethical action, as key to seeing and being, without losing sight of art and aesthetics.